GERMINATION AND VIGOR OF COFFEE SEEDS SUBMITED TO ALUMINIUM STRESS - MACEDO, Célia Maria Peixoto de; LOPES, José Carlos; AMARAL, José Augusto Teixeira do; FONSECA, Aymbiré Francisco Almeida da (Scientia Agraria, 2008)
The objective this work was to evaluate the germination and vigour of coffee seed, cultivars Catuaí Amarelo IAC 86 (Coffea Arabica L.) and Apoatã (Coffea canephora Pierre) at different level of Al. The design was it randomized entirely with four repetitions, in a factorial outline two (cultivars) x 5 (0; 15; 30; 45 e 60 mg Al L-1) of Al concentration. The seeds were placed to germinate in paper-towel rolls, incubated under temperature of the 30 °C and absence of light. After 30 days was determined the germination, and the vigour obtained by the test length of the primary root. The germination and vigour of Catuai Yelow IAC 86 seeds were not influenced by the increase of the aluminum concentration, differing from Apoatã cultivar that the presence of Al revealed sensible in the concentration of 60 mg Al L-1.